2018
DOI: 10.1007/s11747-018-0596-3
|View full text |Cite
|
Sign up to set email alerts
|

Object valuation and non-ownership possession: how renting and borrowing impact willingness-to-pay

Abstract: Prior research on object valuation ignores the effect of non-ownership physical possession types such as renting and borrowing. Evidence from four experiments demonstrates that the valuation (i.e., willingness-to-pay) for rented objects is greater than the valuation for non-possessed or borrowed objects. Borrowed objects are not valued any differently than non-possessed objects. Psychological ownership mediates the relationship between valuation and non-ownership physical possession. Additionally, psychologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 75 publications
1
25
0
Order By: Relevance
“…The findings are consistent with that of Moeller and Wittkowski [60] who stated that non-ownership services is negatively influenced by possession importance ,i.e., consumers are attached to products with full ownership as compared to temporary ownership. Research by Bagga et al [7] also confirmed that rented objects are not valued higher than possessed objects. It was found during the study that individuals who prefer to purchase furniture are not fully convinced with the idea of renting.…”
Section: Discussionmentioning
confidence: 87%
“…The findings are consistent with that of Moeller and Wittkowski [60] who stated that non-ownership services is negatively influenced by possession importance ,i.e., consumers are attached to products with full ownership as compared to temporary ownership. Research by Bagga et al [7] also confirmed that rented objects are not valued higher than possessed objects. It was found during the study that individuals who prefer to purchase furniture are not fully convinced with the idea of renting.…”
Section: Discussionmentioning
confidence: 87%
“…To cope with these difficulties, we kept constant the object to be negotiated-a car-and manipulated the pricing model of how this car was provided to customers. More specifically, in the goods condition, participants were purchasing a car whereas in two alternative services conditions, participants were either leasing the car or entering a pay-per-use contract (e.g., Bagga et al 2018).…”
Section: Methodsmentioning
confidence: 99%
“…First, fractional ownership models of access-based consumption divide property rights across agents, who may each possess one or more of the legal rights to (i) use a good, (ii) profit from its use or sale, (iii) modify the form, substance, or location of the good, or (iv) transfer possession of some or all of these rights between agents (Haase and Kleinaltenkamp 2011). This change impinges on perceived control over access-based goods, a critical antecedent of psychological ownership (Bagga, Bendle, and Cotte 2019). Second, the impermanence associated with access-based goods also threatens psychological ownership (Bardhi and Eckhardt 2017).…”
Section: Change 1: Legal Ownership To Legal Accessmentioning
confidence: 99%
“…Consumers feel less psychological ownership for borrowed than rented goods. Indeed, they feel no more psychological ownership for borrowed goods than goods they merely evaluate (Bagga, Bendle, and Cotte 2019). Marketing actions can be taken to counter threats posed by fractional ownership.…”
Section: Trend 1: the Sharing Economymentioning
confidence: 99%
See 1 more Smart Citation